(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This scientific paper analyzes the importance of artificial intelligence (Artificial Intelligence - AI) based chatbots and virtual tutors in the English language learning process. The main objective of the study is to explore the potential, advantages, challenges, and future prospects of AI technologies in language teaching. The study used methods such as scientific literature analysis, comparative analysis, and monitoring of modern AI platforms. The results showed that chatbots and virtual tutors are effective tools for organizing individual learning, improving pronunciation, identifying grammatical errors, and increasing user motivation. However, there are also challenges such as internet addiction, limited emotional communication, and data security. The research results show that AI technologies will play an increasingly important role in language teaching systems in the future. This article aims to shed light on the role of AI - based educational technologies in the modern educational process.